2017
DOI: 10.3171/2016.11.peds16411
|View full text |Cite
|
Sign up to set email alerts
|

Reoperations within 48 hours following 7942 pediatric neurosurgery procedures

Abstract: OBJECTIVEVarious indicators are used to evaluate the quality of care delivered by surgical services, one of which is early reoperation rate. The indications and rate of reoperations within a 48-hour time period have not been previously reported for pediatric neurosurgery.METHODSBetween May 1, 2009, and December 30, 2014, 7942 surgeries were performed by the pediatric neurosurgery service in the operating r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…In the pediatric population, Mukerji et al report a 17% 30-day reoperation rate at their center in the United Kingdom with 44% of all operations were related to CSF diversion [19]. Similarly, when looking at a 48-hour reoperation rate, CSF shunt placement and hydrocephalus were the major indications (40.8%) reported by Roy et al, which is reflected in our patients as well [20].…”
Section: Discussionsupporting
confidence: 66%
“…In the pediatric population, Mukerji et al report a 17% 30-day reoperation rate at their center in the United Kingdom with 44% of all operations were related to CSF diversion [19]. Similarly, when looking at a 48-hour reoperation rate, CSF shunt placement and hydrocephalus were the major indications (40.8%) reported by Roy et al, which is reflected in our patients as well [20].…”
Section: Discussionsupporting
confidence: 66%
“…Despite the statistical significance, we could not declare later starting time as a risk factor because we lacked information for all the reoperated patients. Roy et al showed that performing surgeries after 5 p.m. is a risk factor for unplanned reoperations [ 20 ]. Similarly, Li et al stated that unplanned reoperations occur more often if the surgeries are finished after hours [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rates of shunt-related unplanned reoperations among all unplanned reoperation patients were 78% and 73.5%, respectively. The overall rate of unplanned shunt-related reoperation among surgeries was 22% (91/410) in the 2-year follow-up in Mukerji et al's study, [13] and 1.47% (117/7942) within 48 hours postoperatively in Roy et al's study [12] . McLaughlin et al reviewed their shunt failure cases, which accounted for 34.4% (63 [pedi/adult: 36/27]/183) of all early unplanned returns and 0.39% (27/6912) among all surgeries within 7 days post-operation [14] .…”
Section: Discussionmentioning
confidence: 87%
“…[ 23 24 25 ] In the adult population, the preventable unplanned shunt implantation return rate has also been proposed as a possible external comparison quality metric. [26] Reviewing the literature on UROR related to CSF diversion, Mukerji et al [13] and Roy et al [12] previously reported that shunt-related procedures accounted for 44% and 40.8% of all pediatric procedures at their study institutions, respectively. The rates of shunt-related unplanned reoperations among all unplanned reoperation patients were 78% and 73.5%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation